Occurrence of Diaporthe species in Eucalyptus globulus, Pinus pinaster and Quercus suber in Portugal. Issue 2 (27th January 2021) - Lopes, Ana Filipa; Batista, Eduardo; Hilário, Sandra; Santos, Liliana; Alves, Artur
Abstract: The genus Diaporthe is a cosmopolitan group of fungi that includes important plant pathogens, endophytes and saprobes with the ability to colonize a wide range of plant hosts. Pathogenic Diaporthe species are often reported to cause symptoms like dieback, stem canker, leaf spots, fruit rots and seed decay resulting in important economic losses on several crops. However, the occurrence of Diaporthe species associated with forest hosts and their pathogenic potential is poorly understood. We studied a collection of Diaporthe isolates obtained from a survey of forest‐related fungal diseases on Eucalyptus globulus, Pinus pinaster and Quercus suber in Portugal. Several Diaporthe species ( D. eres, D. rudis, D. crousii, D. malorum and D. foeniculina ) were found among the studied hosts. Pathogenicity trials were conducted to analyse the pathogenic potential and the ability to colonize putative new hosts. We report the occurrence of D. eres on P. pinaster in Portugal and a new host association with Q. suber . Additional new host reports were as follows: D. malorum and D. crousii on E. globulus, D. foeniculina on Q. suber and D. rudis on P. pinaster . Overall, Diaporthe species were shown to have low pathogenic impact on forest hosts under non‐stress conditions, despite their capability to colonize different hosts during the pathogenicity trials.